Pengaruh Supervisi Akademik Kepala Sekolah, Budaya Kerja dan Disiplin Kerja Guru Terhadap Kompetensi Guru SMP Di Kecamatan Wonosobo Kabupaten Wonosobo - Riyatiningrum, Riyatiningrum; Egar, Ngasbun; Juliejantiningsih , Yovitha (PGRI Kota Semarang, 2024)
Good competence will encourage teachers' work enthusiasm to be able to complete their tasks. Teachers who have good teacher competence areneeded, with high teacher competence it is hoped that they will be able to increase teacher competence. The aim of this research is to analyze the influence of academic supervision, work culture and work discipline together on teacher competence. Quantitative research approach with survey methods. The research population was 227 teachers and the research sample was 145 teachers. Data collection with questionnaires. The research results show that: 1) academic supervision has an effect on teacher competency by 64.5%. 2) work culture influences teacher competency by 76.9%. 3) Work discipline influences teacher competency by 78.1%. 4) academic supervision, work culture and work discipline have an influence on teacher competency by 78.2. The conclusion of this research is that academic supervision, work culture and work discipline have an influence on teacher competency by 78.2%. The author suggests that school principals reflect and evaluate academic supervision, teacher work culture and work discipline.